Combined IFN-β and PLT Detection Can Identify Kawasaki Disease Efficiently - Huijuan, Kan; Yaping, Dong; Bo, Wang; Miao, Hou; Guanghui, Qian; Wenhua, Yan (Frontiers in Pediatrics, 2021)
Objective: To evaluate the value of combined interferon β (IFN-β) and platelet (PLT) detection for Kawasaki disease (KD) identification. Methods: Forty-four children who were newly diagnosed with KD were selected as the KD group. They were divided into acute phase of KD and subacute phase of KD. They were also separated into groups with and without coronary artery disease (CAD) (CAD+ and CAD–, respectively). Meanwhile, 44 children hospitalized with febrile disease and 44 healthy children were selected as a febrile control group and normal control group, whom were attended to at Children's Hospital of Soochow University at the same time. We detected the concentration of IFN-β and PLT of peripheral blood serum for all three groups and analyzed the difference. Results: At acute and subacute phases of KD, both IFN-β and PLT are higher than both the febrile control group and healthy control group, especially at subacute phase; the difference between groups was statistically significant, P < 0.05. Receiver operating characteristic (ROC) curve showed that the areas under the ROC curve (AUCs) of IFN-β and PLT at acute phase of KD were 0.81 and 0.72, respectively; the sensitivity and specificity were 97.22 and 63.64%, and 57.89 and 73.86%, respectively. The AUCs of combined IFN-β and PLT were 0.81 at acute phase and 0.96 at subacute phase of KD, with sensitivity and specificity of 97.22 and 55.26%, and 86.36 and 100%, respectively. The cutoff value of combined IFN-β and PLT detection was IFN-β = 3.51 pg/ml and PLT = 303 × 109/L at acute phase of KD, IFN-β = 4.21 pg/ml and PLT = 368 × 109/L at subacute phase from plot vs. criterion values. However, there are no significant differences between the CAD– group and the CAD+ group for combined IFN-β and PLT, both P > 0.5, neither at acute nor at subacute phase of KD. Conclusion: Combined IFN-β and PLT detection is an efficient biomarker for KD identification. The cutoff values are IFN-β = 3.51 pg/ml and PLT = 303 × 109/L at acute phase of KD and IFN-β = 4.21 pg/ml and PLT = 368 × 109/L at subacute phase.